2008
DOI: 10.1016/j.carbon.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between heats of immersion and limiting capacitances in porous carbons

Abstract: Based on more than 80 carbons, the paper shows that immersion calorimetry into benzene, water and carbon tetrachloride can be used to assess with a good accuracy the limiting capacitance C o at low current densities in both acidic (2 M H 2 SO 4 ) and aprotic (1M tetraethyl ammonium tetrafluoroborate in acetonitrile) electrolytic solutions. The enthalpies of immersion ∆ i H(C 6 H 6 ) andprovide information on C o-acidic , where both the surface area and the oxygen content play a role. On the other hand, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…As shown earlier [15,16], the DFT-based pore size distributions indicate a sharp drop around 0.6-0.7 nm, which suggests that there are no pores below this size. Moreover, the ratios of the enthalpies of immersion into CCl 4 and C 6 H 6 (Table 1) are close to 0.96, the value expected for equal accessibility of the micropores to both liquids [25]. This confirms that the same surface area is accessible to nitrogen, benzene, CCl 4 and the different electrolytes (carbon tetrachloride, with a critical diameter of approximately 0.65 nm, is obviously a convenient analogue for the (C 2 H 5 ) 4 N + ion (0.68 nm) [14]).…”
Section: Resultssupporting
confidence: 55%
“…As shown earlier [15,16], the DFT-based pore size distributions indicate a sharp drop around 0.6-0.7 nm, which suggests that there are no pores below this size. Moreover, the ratios of the enthalpies of immersion into CCl 4 and C 6 H 6 (Table 1) are close to 0.96, the value expected for equal accessibility of the micropores to both liquids [25]. This confirms that the same surface area is accessible to nitrogen, benzene, CCl 4 and the different electrolytes (carbon tetrachloride, with a critical diameter of approximately 0.65 nm, is obviously a convenient analogue for the (C 2 H 5 ) 4 N + ion (0.68 nm) [14]).…”
Section: Resultssupporting
confidence: 55%
“…The participation of oxygen functionalities was further confirmed by the good agreement observed between the experimental capacitances in H 2 SO 4 and those calculated from the enthalpies of immersion of carbons into benzene and water [32].…”
Section: Determination Of the Electrochemical Capacitancesupporting
confidence: 63%
“…Recent results based on the combination of N 2 -physisorption and immersion calorimetry into CH 2 Cl 2 (0.33 nm), C 6 H 6 (0.41 nm) and CCl 4 (0.63 nm) reported that the surface accessible to Et 4 N + was reduced by 20-27 % with respect to the total surface area of carbon monoliths electrodes[47].So far, the most selective physisorption based-approach to assess the surface involved in charges storage is the use of molecules suiting the critical dimension of ions. With the help of carbon tetrachloride (0.63 nm) and norbornadiene (0.65 nm) as convenient probes[6,32,38] for the reliable assessment of the surface area accessible to the cation Et 4 N + ,Figure 3aclearly illustrates that the total surface of a variety of activated carbons is not perceptible for the organic electrolyte. This is particularly remarkable for carbon HK-650-8 with an average micropore size of 0.66 nm, in which Et 4 N + is excluded from 63% of its surface area.…”
mentioning
confidence: 99%
“…In the case of aprotic electrolytes with bulkier ions (e.g. (C 2 H 5 ) 4 NBF 4 in acetonitrile) and ionic liquids such as EMI-TFSI, the accessibility of the micropores may be considerably reduced for carbons with narrow pores (width < 0.7 nm) or showing 'gate' effects at the pores entrance [2,7,9,10]. On the other hand, the contribution from pseudocapacitance effects in the (C 2 H 5 ) 4 NBF 4 /acetonitrile electrolyte appears to be negligible compared to the aqueous media and the supercapacitor performance is essentially based on a double-layer mechanism through the extent of the accessible (effective) surface area of the carbon [2,9,10].…”
Section: Introductionmentioning
confidence: 99%